ChemInform Abstract: Two Nanosized 3d—4f Clusters Featuring Four Ln6 Octahedra Encapsulating a Zn4 Tetrahedron. Issue 35 (September 2015) - Zheng, Xiu‐Ying; Wang, Shi‐Qiang; Tang, Wen; Zhuang, Gui‐Lin; Kong, Xiang‐Jian; Ren, Yan‐Ping; Long, La‐Sheng; Zheng, Lan‐Sun
Abstract Compounds (IV) containing cationic Ln24Zn4 cluster cores crystallize in the cubic space group Fm<alternatives> <![CDATA[$\bar 3$]]> <inline-graphic xlink:href="ark:/27927/pgj2f0rrg68" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>m with Z = 8 (single crystal XRD).